2022
DOI: 10.3390/jcm11133573
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Butyrate Supplementation on Inflammation and Kidney Parameters in Type 1 Diabetes: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: Type 1 diabetes is associated with increased intestinal inflammation and decreased abundance of butyrate-producing bacteria. We investigated the effect of butyrate on inflammation, kidney parameters, HbA1c, serum metabolites and gastrointestinal symptoms in persons with type 1 diabetes, albuminuria and intestinal inflammation. We conducted a randomized placebo-controlled, double-blind, parallel clinical study involving 53 participants randomized to 3.6 g sodium butyrate daily or placebo for 12 weeks. The prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…De Groot et al [ 24 ] found that oral butyrate supplementation for 1 month did not result in any significant changes in adaptive or innate immunity, or in any of the other outcome variables in humans with longstanding T1D. Similarly, Tougaard et al [ 25 ] reported that 12 weeks of butyrate supplementation did not reduce intestinal inflammation in persons with T1D, albuminuria, and intestinal inflammation. Our data in mouse models of T1D seem to contrast previous studies showing no effect of butyrate in human T1D.…”
Section: Discussionmentioning
confidence: 99%
“…De Groot et al [ 24 ] found that oral butyrate supplementation for 1 month did not result in any significant changes in adaptive or innate immunity, or in any of the other outcome variables in humans with longstanding T1D. Similarly, Tougaard et al [ 25 ] reported that 12 weeks of butyrate supplementation did not reduce intestinal inflammation in persons with T1D, albuminuria, and intestinal inflammation. Our data in mouse models of T1D seem to contrast previous studies showing no effect of butyrate in human T1D.…”
Section: Discussionmentioning
confidence: 99%
“…Mean participant age ranged from 5.5 to 56 years, and T1D duration ranged from 1.5 to 30 years. Six studies implemented MMA supplementation for 3 months [30][31][32][33]35], with one study using less than 3 months [34] and three studies exceeding 3 months [29,34,37].…”
Section: Basic Characteristics Of the Included Studiesmentioning
confidence: 99%
“… 87 , 88 Butyrate has received a lot of attention in recent studies because it seems to play a key role in the pathogenesis of obesity and diabetes. 81 , 89 - 91 …”
Section: Scfas-metabolic Pathologies Axismentioning
confidence: 99%
“…87,88 Butyrate has received a lot of attention in recent studies because it seems to play a key role in the pathogenesis of obesity and diabetes. 81,[89][90][91] Propionate and butyrate may contribute to metabolic health by activation of intestinal gluconeogenesis (IGN). 84,92 This activation permitted to explain of the anti-obesity and antidiabetic effects of dietary fibers.…”
Section: Scfas and Obesitymentioning
confidence: 99%